# Quiz-1

Question 1

Time: 00:00:00
Find the parameters a and b included in the linear function f(x) = a x + b so that f -1 (2) = 3 and f -1 (-3) = 6, where f -1 (x) is the inverse of function f.

a = - 5 / 3 and b = 7

a = - 5 / 3 and b = 7

a = 5 / 3 and b = 7

a = 5 / 3 and b = 7

a = -3 / 5 and b = 7

a = -3 / 5 and b = 7

a = 3 / 5 and b = -7

a = 3 / 5 and b = -7

Once you attempt the question then PrepInsta explanation will be displayed.

Start

Question 2

Time: 00:00:00
Given f(x) = x3 + 2 x, complete the table of values given below and find f -1(3) and f -1(- 12) respectively.

 x f(x) 0 0 1 3 2 12

-1, -2

-1, -2

1, 2

1, 2

1, -2

1, -2

-1, 2

-1, 2

Once you attempt the question then PrepInsta explanation will be displayed.

Start

Question 3

Time: 00:00:00
If f(x) = ln(x) + 4 x - 8, what is the value of f -1(- 4)?

-1

-1

1

1

2

2

-2

-2

Once you attempt the question then PrepInsta explanation will be displayed.

Start

Question 4

Time: 00:00:00
Find an equation for the inverse of the function given f(x) = 3x - 2

f-1(x) = (x+2) / 3

f-1(x) = (x+2) / 3

f-1(x) = (x-2) / 2

f-1(x) = (x-2) / 2

f-1(x) = 3(3x-2) / 2

f-1(x) = 3(3x-2) / 2

f-1(x) = (2x-1) / 2

f-1(x) = (2x-1) / 2

Once you attempt the question then PrepInsta explanation will be displayed.

Start

Question 5

Time: 00:00:00
Find inverse of f(x) = (x+2) / (4x - 4)

f-1(x) = (4x + 2) / (4x - 1)

f-1(x) = (4x + 2) / (4x - 1)

f-1(x) = (4x + 1) / (4x - 2)

f-1(x) = (4x + 1) / (4x - 2)

f-1(x) = (2x + 4) / (4x - 1)

f-1(x) = (2x + 4) / (4x - 1)

f-1(x) = (2x + 2) / (4x - 1)

f-1(x) = (2x + 2) / (4x - 1)

Once you attempt the question then PrepInsta explanation will be displayed.

Start

Question 6

Time: 00:00:00

Find inverse of f(x) = log5(2x - 1)

f-1(x) = (2x + 1) / 2

f-1(x) = (2x + 1) / 2

f-1(x) = (5y + 1) / 2

f-1(x) = (5y + 1) / 2

f-1(x) = (2x + 1) / 5

f-1(x) = (2x + 1) / 5

f-1(x) = (5x + 1) / 2

f-1(x) = (5x + 1) / 2

Once you attempt the question then PrepInsta explanation will be displayed.

Start

Question 7

Time: 00:00:00
Given h(x)=5−9x find h−1(x) .

h−1(x) = (5-x) / 9

h−1(x) = (5-x) / 9

h−1(x) = (1-x) / 9

h−1(x) = (1-x) / 9

h−1(x) = (9-x) / 9

h−1(x) = (9-x) / 9

h−1(x) = (9-x) / 5

h−1(x) = (9-x) / 5

Once you attempt the question then PrepInsta explanation will be displayed.

Start

["0","40","60","80","100"]
["Need more practice!","Keep trying!","Not bad!","Good work!","Perfect!"]

Personalized Analytics only Availble for Logged in users

Analytics below shows your performance in various Mocks on PrepInsta

Your average Analytics for this Quiz

Rank

-

Percentile

0%

Get over 200+ Courses under One Subscription

Don’t settle Learn from the Best with PrepInsta Prime Subscription

Learn from Top 1%

## One Subscription, For Everything

The new cool way of learning and upskilling -

Limitless Learning

One Subscription access everything

Job Assurance